(29b-3)-7(4b+3)=-4

Simple and best practice solution for (29b-3)-7(4b+3)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (29b-3)-7(4b+3)=-4 equation:


Simplifying
(29b + -3) + -7(4b + 3) = -4

Reorder the terms:
(-3 + 29b) + -7(4b + 3) = -4

Remove parenthesis around (-3 + 29b)
-3 + 29b + -7(4b + 3) = -4

Reorder the terms:
-3 + 29b + -7(3 + 4b) = -4
-3 + 29b + (3 * -7 + 4b * -7) = -4
-3 + 29b + (-21 + -28b) = -4

Reorder the terms:
-3 + -21 + 29b + -28b = -4

Combine like terms: -3 + -21 = -24
-24 + 29b + -28b = -4

Combine like terms: 29b + -28b = 1b
-24 + 1b = -4

Solving
-24 + 1b = -4

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 1b = -4 + 24

Combine like terms: -24 + 24 = 0
0 + 1b = -4 + 24
1b = -4 + 24

Combine like terms: -4 + 24 = 20
1b = 20

Divide each side by '1'.
b = 20

Simplifying
b = 20

See similar equations:

| 4x=2y-yx | | -(3x-6y-9)= | | 2/3k-9=5 | | -4=1x-12 | | 6u^2-22uv+20v^2=0 | | 5p-(-10)=-5 | | 23y/30-4=96y/5 | | 16x^2+18x=19 | | 37-63= | | 0=2.15+9.6x+(.5)(-9.81)(x^2) | | k+9=7.5 | | 5x-3(y-2)=2x+21 | | x+.14x=1234.62 | | 28=-2(3x-5) | | 70=7000/12*r | | 37+63= | | f(x+9)=x^2+2x+3 | | 4x^1/3-9x^1/3 | | 6x(3+4)=(6+3)+4 | | 3(12-x)=16-2 | | 15=4a | | p-2(3-2p)=2p+9 | | 3y-7x=28 | | x+(x+1.2)+(x-1.2)=28.5 | | (2x-4)*2=26 | | 75=5000/12*r | | p-18=59 | | 6a+18=6 | | 8.5+6*h/2=241.18 | | 99x+10=189 | | 1750-140= | | 3[(5x+3)-4]=4(2x-3) |

Equations solver categories